2009
DOI: 10.2527/jas.2008-0913
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slow-release urea on nitrogen balance and portal-drained visceral nutrient flux in beef steers

Abstract: Two experiments were conducted to evaluate the effects of slow-release urea (SRU) versus feed-grade urea on portal-drained visceral (PDV) nutrient flux, nutrient digestibility, and total N balance in beef steers. Multi-catheterized steers were used to determine effects of intraruminal dosing (Exp. 1; n = 4; 319 +/- 5 kg of BW) or feeding (Exp. 2; n = 10; 4 Holstein steers 236 +/- 43 kg of BW and 6 Angus steers 367 +/- 46 kg of BW) SRU or urea on PDV nutrient flux and blood variables for 10 h after dosing. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 34 publications
3
40
1
8
Order By: Relevance
“…In contrast with the present findings (Table 4), Ribeiro et al (2011) found no differences in N digestibility between urea and Optigen® II treatments. According to the findings of this study, it could be suggested that post-ruminal N concentration would increase when Optigen® II is used to replace urea completely in a supplement, and therefore increased faecal N levels could be expected (Taylor-Edwards et al, 2009a). …”
Section: Resultsmentioning
confidence: 99%
“…In contrast with the present findings (Table 4), Ribeiro et al (2011) found no differences in N digestibility between urea and Optigen® II treatments. According to the findings of this study, it could be suggested that post-ruminal N concentration would increase when Optigen® II is used to replace urea completely in a supplement, and therefore increased faecal N levels could be expected (Taylor-Edwards et al, 2009a). …”
Section: Resultsmentioning
confidence: 99%
“…(TAYLOR-EDWARDS et al, 2009). Estes compostos não têm sido tão vantajosos como a ureia, pois uma parte substancial do NNP neles presente pode não ser convertida em NH 3 pelo rúmen, reduzindo a sua incorporação à proteína microbiana (GALO et al, 2003;FIRKINS et al, 2007).…”
Section: Ureia Encapsulada Na Alimentação De Vacas Leiteirasunclassified
“…Não foram encontradas diferenças no pH, na produção total e proporção molar dos ácidos graxos voláteis. (HUNTINGTON et al, 2006;GOLOMESKI et al, 2006;TAYLOR-EDWARDS et al, 2009;HIGHSTREET et al, 2010;INOSTROZA et al, 2010;PINOS-RODRÍGUEZ et al, 2010;XIN et al, 2010). No entanto, as concentrações de N-NH 3 nos tratamento com ureia de liberação lenta e com proteína isolada de soja continuou declinando.…”
Section: Fermentação Ruminalunclassified
“…Os compostos de uréia de liberação lenta que tem sido utilizados em dieta de ruminantes incluem biureto, amiréia, uréia fosfato e uréia com revestimentos a base de óleos, formaldeído e polímeros (Taylor-Edwards et al, 2009).…”
Section: Uréia De Liberação Lenta Na Alimentação De Ruminantesunclassified
“…A utilização de uréia de liberação lenta in vivo apresenta uma taxa mais lenta de liberação de nitrogênio amoniacal do que a uréia e pode efetivamente modular as concentrações de nitrogênio amoniacal quando substituído por uréia (Huntington et al, 2006;Golomeski et al, 2006;Taylor-Edwards et al, 2009;Cherdthong et al, 2010;Highstreet et al, 2010;Inostroza et al, 2010;Pinos-Rodríguez et al, 2010;Xin et al, 2010).…”
Section: Uréia De Liberação Lenta Na Alimentação De Ruminantesunclassified